Shear wave elastography based analysis of changes in fascial and muscle stiffness in patients with chronic non-specific low back pain - Liu, Kun; Zhao, Tong; Zhang, Yang; Chen, Lili; Zhang, Haoran; Xu, Xiqiang; Yuan, Zenong; Zhang, Qingyu; Dong, Jun (Frontiers in Bioengineering and Biotechnology, 2024)
Background: The quantitative assessment of individual muscle and fascial stiffness in patients with low back pain remains a challenge. This study aimed to compare the stiffness of the thoracolumbar fascia (TLF), erector spinae (ES), and multifidus (MF) in patients with and without chronic non-specific low back pain (CNLBP) using shear wave elastography (SWE). It also sought to explore the relationship between muscle and fascial stiffness and the levels of pain and dysfunction in patients with CNLBP. Methods: In this cross-sectional study, 30 patients with CNLBP and 32 healthy controls were enrolled. Stiffness of the TLF, ES, and MF was measured using SWE, and Young's modulus values were recorded. The numeric rating scale (NRS) for quantifying pain intensity and the Oswestry Disability Index (ODI) scores were recorded for the case group to examine their correlations with the resilience index. Results: The CNLBP group exhibited significantly higher shear modulus values at the L4-5 bilateral TLF, ES, and MF compared to the control group. Comparable findings were observed for the right ES and left MF at L1-2. Strong correlations were observed between the shear modulus of the bilateral TLF at L4-5 and the NRS scores. Moderate correlations were noted between the shear modulus of the ES and MF at L4-5 and the NRS scores. Additionally, the shear modulus of the MF on the left side of L1-2 showed similar correlations. Strong correlations were observed between the shear modulus of the bilateral TLF at L4-5 and the ODI scores. Moderate correlations were observed between the shear modulus of the right TLF, ES, and MF at L1-2, as well as the bilateral MF at L4-5, and the ODI scores. No significant correlations were found at other measurement sites. Conclusion: In patients with CNLBP, the stiffness of the lumbar fascia and muscles is generally higher than in individuals without LBP. However, this increase is not uniform across all lumbar regions, with the most significant changes observed in the L4-5 segments. In addition, higher stiffness may be associated with pain and dysfunction, primarily manifested in the TLF.